OSCE: Management of hypernatremic dehydration in neonates - Nidhi Jain; Ashish Jain (Wolters Kluwer Medknow Publications, 2019)
Hypernatremic dehydration is a neonatal morbidity commonly seen in exclusively breast-fed neonates due to inadequate breast milk intake. This problem is generally missed by native practitioners as the degree of dehydration can be underestimated due to fluid shifts. Neonates of primiparous mothers, neonates born via caesarean section and those who experience greater weight loss in the first week of life are at higher risk of developing hypernatremic dehydration. No consensus treatment guidelines exist till date. Complications of hypernatremic dehydration like cerebral edema usually occur during improper correction.